Embolization with Histoacryl Glue of an Anastomotic Pseudoaneurysm following Surgical Repair of Abdominal Aortic Aneurysm - Walid, Ayesha (Hindawi Publishing Corporation, 2013)
We report a 62-year-old female who had surgical repair of abdominal aortic aneurysm with a bifurcated graft 2 years ago. She presented with a distal anastomotic pseudoaneurysm which was successfully embolized with histoacryl glue. Only one such similar case has been reported in the literature so far (Yamagami et al. (2006)).